(untitled) (Journal of Science and Technology, 2016)
Large numbers of test stimuli impact on the time and cost of test application. Hence there is the need to keep numbers of test stimuli low while maintaining as high fault coverage as possible. In this paper, static compaction of test stimuli is seen as a minimization problem. The task of static compaction of a set of test stimuli has been formulated as a minimum covering problem. Based on the concept of minimization, a method of static compaction has been developed. Results of experiments conducted to evaluate the method are also presented. The method achieved a sig- nificant compaction of sets of test stimuli that had previously been compacted by means of a test generation algorithm that features dynamic compaction.